Analysis of Longitudinal Cracks in Multilayered Beams with Account of the Material Nonlinearity - Rizov, V.I. (Проблемы прочности, 2017)
The present paper reports a theoretical study of longitudinal fracture in multilayered beams with taking into account the material non-linearity. The study was performed in terms of the strain energy release rate by using the classical beam theory. The analysis developed holds for cracked beams whose layers may have different thickness. Besides, the mechanical behaviour of each layer may be described by different non-linear stress-strain relations. Also, the crack may be located arbitrary along the beam height. The strain energy release rate was expressed in a function of the bending moments and axial loads in the cross-sections ahead and behind the crack front. In this way, non-linear fracture analyses of multilayered beams can be carried-out in a closed analytical form. It was shown that the analysis developed is a useful tool for the understanding of non-linear longitudinal fracture in multilayered beam configurations.